Pengaruh Media Sosial terhadap Gaya Hidup Remaja di SMA Negeri 1 Cikalongwetan Kabupaten Bandung Barat - Lumban Gaol, Angelina; Pribowo, Pribowo; Winarni, Endah Dwi (Politeknik Kesejahteraan Sosial Bandung, 2023)
Social media is the one of the example of new media (as we called internet) that can influence the lifestyle of teenagers. The emergence of this new media can affect lifestyle among the people which become easier when establishing communication. The main focus for this observation is about lifestyle which is used by the users of social media. The aim of this observation is for knowing the sosial media’s influence for the students of SMA Negeri 1 Cikalongwetan in their lifestyle. The methode that is used for this observation is quantitative method using simple random sampling technique. Data collection from the questioner and then is processed using Statistical Package of the Social Science (SPSS). The result from this observation showing that social media has the significant influence toward the lifestyle which is showed by the calculating of r equals as 0,709. Showing the correlation value which is strong enough (>0,600) with the significant (0,000<0,05). The big influence of social media in SMA Negeri 1 Cikalongwetan’s students for their lifestyle can be seen from Adjucted R Square is about 50,3% and the rest is influenced by the others variable out of this observation about 49,7%.